The decreased oxygen uptake during progressive exercise in ischemia-induced heart failure is due to reduced cardiac output rate - Rolim,N.P.L. (2006)
We tested the hypothesis that the inability to increase cardiac output during exercise would explain the decreased rate of oxygen uptake (VO2) in recent onset, ischemia-induced heart failure rats. Nine normal control rats and 6 rats with ischemic heart failure were studied. Myocardial infarction was induced by coronary ligation. VO2 was measured during a ramp protocol test on a treadmill using a metabolic mask. Cardiac output was measured with a flow probe placed around the ascending aorta. Left ventricular end-diastolic pressure was higher in ischemic heart failure rats compared with normal control rats (17 ± 0.4 vs 8 ± 0.8 mmHg, P = 0.0001). Resting cardiac index (CI) tended to be lower in ischemic heart failure rats (P = 0.07). Resting heart rate (HR) and stroke volume index (SVI) did not differ significantly between ischemic heart failure rats and normal control rats. Peak VO2 was lower in ischemic heart failure rats (73.72 ± 7.37 vs 109.02 ± 27.87 mL min-1 kg-1, P = 0.005). The VO2 and CI responses during exercise were significantly lower in ischemic heart failure rats than in normal control rats. The temporal response of SVI, but not of HR, was significantly lower in ischemic heart failure rats than in normal control rats. Peak CI, HR, and SVI were lower in ischemic heart failure rats. The reduction in VO2 response during incremental exercise in an ischemic model of heart failure is due to the decreased cardiac output response, largely caused by depressed stroke volume kinetics.